Temperature sensitivity thresholds to warming and cooling in phenophases of alpine plants - Meng, Fandong; Zhou, Yang; Wang, Shiping; Duan, Jichuang; Zhang, Zhenhua; Niu, Haishan; Jiang, Lili; Cui, Shujuan; Li, Xin’e; Luo, Caiyun; Zhang, Lrirong; Wang, Qi; et al. (Climatic change, 2016)
The assumption of a linear relationship between temperature and phenophases may be misleading. Furthermore, a lack of understanding of the changes in temperature sensitivity of phenophases to changes in temperature strongly limits our ability to predict phenological change in response to climate change. We investigated the timing of seven phenophases of six alpine plant species to test the hypothesis of nonlinear responses in their temperature sensitivities to warming and cooling, using a reciprocal transplant experiment along a 3200–3800 m mountain slope gradient. Our results supported our hypothesis and showed that there were different thresholds in temperature sensitivity of phenophases to warming and cooling. Moreover, linear temperature sensitivity models significantly underestimated advances and delays of phenophases within the thresholds of temperature change. The nonlinear temperature sensitivity of phenophases is best explained by plastic and adaptive responses of phenophases to temperature change gradients. Therefore, our results suggest that the thresholds of temperature sensitivity for different species should be determined and that nonlinear models of temperature sensitivity may be essential to predict accurately phenological responses to climate change.